Elucidation of antioxidant properties of wood bark derived saturated diarylheptanoids: a comprehensive (DFT-supported) understanding - Ponomarenko, Jevgenija; Trouillas, Patrick; Martin, Nicolas; Dizhbite, Tatyana; Krasilnikova, Jelena; Telysheva, Galina (Phytochemistry, 2014)
A series of diarylheptanoids, namely 1,7-bis-(3,4-dihydroxyphenyl)-heptan-3-one-5-O-D-xylopyranoside (oregonin), 1,7-bis-(3,4-dihydroxyphenyl)-3-hydroxyheptane-5-O-β-D-xylopyranoside and 1,7-bis-(4-hydroxyphenyl)-heptane-3-one-5-O-β-D-glucopyranoside (platyphylloside), were isolated from the bark of alder family trees, a species widely spread over in Europe. As antioxidants, these natural polyphenols have a promising potential in various fields of application, but their redox reactivity is insufficiently characterized. In this work, their antioxidant activity is described using assays based on DPPH and ABTS(+) radical scavenging, oxygen anion radicals (O2(-)) quenching. The standardized ORAC assay was also achieved, which measures the capacity to protect fluorescent molecules against oxidative degradation. The measured antioxidant activity was higher than that of the well-known antioxidant and biologically active diarylheptanoid curcumin. Molecular modeling was used to rationalize the differences in activity and the mechanisms of action. Thermodynamic descriptors mainly O-H bond dissociation enthalpies (BDEs) establish a clear structure-activity relationship.
Keywords: kůra rostlin; vztahy mezi strukturou a aktivitou; Diarylheptanoids; Structure-Activity Relationship; olše; Antioxidants; Plant Bark; diarylheptanoidy; Alnus; dřevo; antioxidancia; Wood